Maja Fruit (Crescentia cujete L.) Potential as a Laxative in Mice - Teodhora, Teodhora; Manalu, Rosario Trijuliamos; Kusuma, Ika Maruya; Azizah, Shandy (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2023)
Constipation is a digestive disorder that anyone with symptoms of complex, uneven, and irregular bowel movements commonly experiences. This study aims to determine the laxative effect of maja extract (Crescentia cujete L.) on male white mice (Mus musculus) induced by loperamide. This fruit has been reported to be used as an analgesic, anti-inflammatory, and for digestive system disorders. The method used to test laxative activity is the intestinal transit method. Parameters observed included stool weight, defecation frequency, feces consistency, and not passage length in the intestine of mice. The extract was administered orally at a dose of 125 mg/kg BW, 250 mg/kg BW and 500 mg/kg BW; as a comparison, a negative control (CMC Na) and a positive control (docusate sodium) were used. Phytochemical screening of maja extract contains alkaloids, flavonoids, tannins, and saponins. The best results were obtained maja fruit can provide a therapeutic laxative effect through the molecular mechanism of secondary metabolites in loperamide-induced test animals.